Sperm Activation of Asthenospermic Infertile Patient by Using Swim-up and Swim-down Techniques - Rana F. M. Al- Dulaimi (Institute of Medico-legal Publications Pvt Ltd, 2020)
The study included ten semen samples collected from infertile patients with asthenospermia . Each sample was divided into two equal parts where the sperm were activated by swim up techniques up on a part of the sample while the second part was used to activate the sperm by swim down . The results showed a significant decrease (p < 0.05) in both the recovered sperm concentration and the concentration of leukocytes after activation with both techniques compared with their values before activation . A significant increase was observed in the percentage of sperm motility style A+B and a significant decrease in sperm motility percent style C after activation compared with their values before activation. The significant difference was not observed ( p >0.05) when comparing between the two techniques . There was also no significant difference ( p > 0.05) in the percentage value of the abnormal sperm percent before and after activation. The study concludes that the techniques of swim up and swim down are effective in activating the sperm of infertile patients who are infected with asthenospermia .